Particulate emission reduction from biomass burning in small combustion systems with a multiple tubular electrostatic precipitator - Panich Intra (2018)
Biomass utilization via combustion is gaining an increasingly important role worldwide in heat and power production. Emissions of particulate matter from biomass burning have drawn considerable attention because of concern over their possible toxicity and implications for human health. For small-scale applications, it is desirable to employ a simple, compact, and inexpensive solution to avoid air quality problems related to biomass combustion. Electrostatic precipitation is a very reliable method to control particulate emissions from boilers, incinerators, and other industrial processes. It is therefore applied to small combustors. In this work, a simple, compact, and cost-effective multiple tubular electrostatic precipitator was designed and evaluated theoretically and experimentally for removal of particulate matter from a small biomass combustor. The precipitator consisted of a simple array of coaxial discharge electrodes placed along the axis of each cylindrical collection tube. The discharge electrodes were connected to the positive high-voltage supply, while the cylindrical collection tubes were grounded. The positive high-voltage supply was used to produce the corona discharge field between individual discharge electrode and collection tube. The particle-laden exhaust gas flow from the small biomass furnace was directed across the corona discharge field and then charged. The charged particles were deflected outward in a radial direction and deposited on the collection tube wall. The overall collection efficiency of the electrostatic device was evaluated as a mass loading ratio of the difference at inlet and outlet to the particle loading at the inlet of the device. It was found that about 70% overall collection efficiency can be achieved with a relatively simple multiple tubular electrostatic precipitator design. The device appeared to be a promising tool for reduction of particulate matter in flue gas from a small biomass combustion system. Copyright © Taylor & Francis Group, LLC.